Alcohol-related disease - Tiago Castro Pinto; Susana G. Rodrigues (Nutrimentum et Curae)
Alcohol, the most consumed drug in the world, is responsible for millions of deaths and a significant of disability-adjusted life years. Alcohol-related liver disease is the most recognized disease related to heavy ethanol consumption, whose pathophysiology we will cover extensively. However, pancreatitis, dilated cardiomyopathy, alcohol-related neurological diseases and other topics will be reviewed with detailed pathophysiological mechanisms and unifying concepts. Abstinence is the most effective treatment for alcohol-related disease, and an international effort should be made to promote a marked reduction in alcohol consumption.